A Comparative Analysis of Uptake and Accumulation Pattern of Iron in Indian Barnyard Millet and Rice (Bangladesh Journal of Botany, 2024)
The present study focuses on how Fe accumulation and re-mobilization pattern differs between Indian barnyard millet and rice at different growth stages. Screening Indian barnyard millet accessions resulted in identification of MDU 1, as the highest accumulator of Fe in seeds. Further, pot culture studies were conducted with MDU 1, ACM-16-5 (low seed Fe accumulating barnyard millet accession) and a rice variety (ASD 16). The accumulation pattern of Fe in the seeds of MDU 1, ACM-16-5 and ASD 16 was influenced by re-mobilization of nutrients from non-flag leaf, flag leaf, root and stem during flowering and maturity. The expression of metal homeostasis genes such as YSL16, ZIP2 and ZIP8 in leaf and root tissues of MDU 1 at the flowering stage appear to play a vital role in Fe absorption and translocation. Remobilization of nutrients from various plant parts to seeds at flowering and maturity stage is efficient in barnyard millet.Bangladesh J. Bot. 53(2): 257-264, 2024 (June)